Prevalence, correlates, and the association of psychotic-like experience with impaired quality of life among Chinese patients with diabetes mellitus: a large-scale cross-sectional study - Li, Zhiqi; Liu, Leiling; Wang, Chun; Peng, Wanwan; Wu, Qiuxia; Peng, Pu; Zhang, Jingjing (Frontiers in Psychiatry, 2025)
IntroductionWhile numerous studies have demonstrated a strong association between diabetes mellitus (DM) and psychotic disorders, the relationship between DM and psychotic-like experiences (PLEs)—a subclinical phenomenon at the early stage of the psychosis continuum—remains largely underexplored. This study aimed to investigate the prevalence, correlates, and impact of PLEs on quality of life (QOL) in a large sample of Chinese patients with DM.MethodsA total of 816 patients with DM and 302 controls were recruited via convenience sampling. PLEs, insomnia, depression, anxiety, stress, diabetes distress, and QOL were assessed using validated questionnaires, alongside demographic and diabetes-related data. Multiple logistic regression models were employed to determine the independent association between DM and PLEs, as well as the correlates of PLEs among patients with DM. Analysis of covariance was used to examine the independent relationship between PLEs and QOL.ResultsThe prevalence of any PLEs, frequent PLEs, and clinically relevant PLEs in the DM group was 74.75%, 35.29%, and 13.85%, respectively, compared to 49.67%, 4.30%, and 0.66% in controls. DM was independently associated with higher risks of any PLEs (AOR 1.48, 95% confidence interval (CI) 1.04-2.10), frequent PLEs (AOR 6.56, 95% CI 3.44-12.51), and clinically relevant PLEs (AOR 10.34, 95% CI 2.36-45.35). Age, smoking, diabetes distress, depression, and stress were significant correlates of PLEs. PLEs were significantly associated with lower QOL across all domains.DiscussionPatients with DM are at a substantially increased risk for PLEs, which significantly impair their QOL. This highlights the need for regular PLEs assessments in routine diabetes care and suggests that interventions targeting depression, diabetes distress, stress, and smoking may help mitigate the burden of PLEs in this population. Future studies should further explore the potential underlying mechanism.